2015
DOI: 10.1507/endocrj.ej14-0544
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled, double-blind, phase 3 trial to evaluate the efficacy and safety of anagliptin in drug-naïve patients with type 2 diabetes

Abstract: Abstract. The aim of this study was to evaluate the efficacy and safety of anagliptin in drug-naïve patients with type 2 diabetes in a double-blind randomized placebo-controlled study. A total of 109 patients were randomized to 100 mg (n=37) or 200 mg (n=33) anagliptin twice daily or placebo (n=39). The primary objective was to alter HbA1c levels from baseline at a 24-week endpoint. The overall baseline mean age and body mass index were 56.20 ± 9.77 years and 25.01 ± 2.97 kg/m 2 , respectively, and the HbA1c l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…After screening titles and abstracts, we retrieved 343 reports for full text screening. A total of 62 RCTs, including 13 from journals 10 11 12 13 14 15 16 17 18 19 20 21 22 23 and 49 from the trial registry (available from https://clinicaltrials.gov ) were included in the final analysis. The details of the study selection flow are described in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After screening titles and abstracts, we retrieved 343 reports for full text screening. A total of 62 RCTs, including 13 from journals 10 11 12 13 14 15 16 17 18 19 20 21 22 23 and 49 from the trial registry (available from https://clinicaltrials.gov ) were included in the final analysis. The details of the study selection flow are described in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this meta-analysis, which included 10 RCTs, subgroup analyses were conducted based on the nature of the control group, either ACG or PCG. One study included a placebo in the control group, [19] and the other had no drug in the control group [16] ; these 2 studies were analyzed in the PCG. Eight studies that included an oral AHA in the control group were analyzed in the ACG.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the meta-analysis included only 2 RCTs involving a small number of subjects (n = 99), which might be insufficient to compare the HbA1c-lowering effect of anagliptin versus placebo. Out of the 2 included studies, 1 demonstrated a significant HbA1c reduction (0.73% more) with anagliptin than placebo, [19] while the other did not show a significant difference. [16] The low baseline HbA1c (7.2% ± 0.5%) in the later study may account for the nonsignificant HbA1c-lowering effect of anagliptin over placebo.…”
Section: Discussionmentioning
confidence: 99%
“…22 Vildagliptin was launched later than the nonpeptide sitagliptin, 23 which is a once-daily, noncovalent DPP-4 inhibitor approved by the FDA in 2006. Subsequently, with the exception of twice-daily anagliptin, 24 seven other oncedaily DPP-4 inhibitors have been launched in various countries (saxagliptin, 25 alogliptin, 26 linagliptin, 27 teneligliptin, 28 gemigliptin, 29 evogliptin, 30 and gosogliptin, 31 see Figure 1). In addition, novel long-acting DPP-4 inhibitors with less frequent dosing regimens have been developed; two once-weekly DPP-4 inhibitors, omarigliptin 32 and trelagliptin, 33 were launched in Japan in 2015 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%